2008
DOI: 10.1007/s10800-008-9740-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of Gd(III) and Nd(III) on reactive cathode material in molten fluoride media

Abstract: The electrochemical reduction of two lanthanides (neodymium Nd and gadolinium Gd) was investigated in the 800-950°C temperature range on nickel and copper electrodes. These materials react with lanthanides (Ln) to form intermetallic compounds. The formation mechanism of the alloys was determined by coupling electrochemical techniques and Scanning Electron Microscopy (SEM) after electrolyses runs; this also allowed the identification of the binary compounds formed. In addition, from the electrochemical results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…As reported in Ref. [11], the voltammogram peaks correspond to the formation of Ni 5 Nd, Cu 6 Nd, Ni 5 Gd and Cu 6 Gd, respectively. (ii) introduction of a EC into the bath for an electrolysis time of around 3 h to recover the alloy; this electrode was then removed from the experimental medium.…”
Section: Extraction Experimental Proceduressupporting
confidence: 58%
See 2 more Smart Citations
“…As reported in Ref. [11], the voltammogram peaks correspond to the formation of Ni 5 Nd, Cu 6 Nd, Ni 5 Gd and Cu 6 Gd, respectively. (ii) introduction of a EC into the bath for an electrolysis time of around 3 h to recover the alloy; this electrode was then removed from the experimental medium.…”
Section: Extraction Experimental Proceduressupporting
confidence: 58%
“…Reference [11] dealt with our results on the electrochemical behaviour of Nd(III) and Gd(III) on reactive nickel and copper electrodes. The study showed that Nd(III) and Gd(III) could be reduced by alloying with the cathodic material (Cu or Ni) at far more anodic potentials than on an inert cathode; this so-called 'depolarization effect'allows the theoretical extraction efficiency of these lanthanides to be enhanced up to 100%.…”
Section: Previous Results Obtained On the Electrochemical Behaviour Omentioning
confidence: 99%
See 1 more Smart Citation
“…Gibbs energies of formation of intermetallic compounds at 1113K were further calculated and compared with data measured by Nourry et al [40] in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Using direct synthesis calorimetry, Guo and Kleppa [37,38] measured the standard enthalpies of formation of GdNi and GdNi 5 compounds. Nourry et al [40] measured experimentally the Gibbs energies of formation of some Gd-Ni intermetallic compounds. The predicted enthalpies of formation of Gd-Ni alloys from the semi-empirical model of Miedema et al [39] are also available in the literature.…”
Section: Thermodynamic Datamentioning
confidence: 99%